Understanding patients' perceptions of asthma control: a qualitative study. Issue 6 (28th June 2018) - Bidad, Natalie; Barnes, Neil; Griffiths, Chris; Horne, Rob
Asthma control is suboptimal for many sufferers despite the existence of effective treatments. Patients' self-management is influenced by their perceptions of asthma and its treatment. This study explored sufferers' perceptions of asthma control and their influence on self-management behaviours. Participants (n=42) recruited from primary and secondary care asthma clinics in London in the UK each underwent a qualitative interview exploring perceptions and experiences of asthma control. Purposive sampling ensured variation in disease severity, degree of asthma control, age and socioeconomic status. Grounded theory was employed in thematic analysis of transcribed interviews. Five themes relating to perceptions of asthma control and self-management were identified: personal meaning of control, intermittent prevention, compromising control to avoid medication, pharmacological agents overemphasised in control and the role of asthma review in control. Within the first theme, some participants had an internal barometer of the level of symptoms that indicated their asthma was getting "out of control" that was set much higher than Asthma Control Test criteria. The findings provide new insights into patients' perceptions of asthma control. Symptoms indicative of poor control were often tolerated as part of living with asthma. Identification of barriers and drivers to self-management highlight potential targets for strategies aimed at optimising asthma management. For many asthma sufferers "control" means avoidance of deterioration which results in ineffective self-management http://ow.ly/paFA30jWAez